Shrub expansion raises both aboveground and underground multifunctionality on a subtropical plateau grassland: coupling multitrophic community assembly to multifunctionality and functional trade-off - Ding, Leilei; Chen, Hong; Wang, Mengya; Wang, Puchang (Frontiers in Microbiology, 2024)
Introduction: Shrubs have expanded into grasslands globally. However, the relative importance of aboveground and underground diversity and the relative importance of underground community assembly and diversity in shaping multifunctionality and functional trade-offs over shrub expansion remains unknown.In this study, aboveground and underground multitrophic communities (abundant and rare archaea, bacteria, fungi, nematodes, and protists) and 208 aboveground and underground ecosystem properties or indicators were measured at three stages (Grass, Mosaic, Shrub) of shrub expansion on the Guizhou subtropical plateau grassland to study multifunctionality and functional trade-offs.The results showed that shrub expansion significantly enhanced aboveground, underground, and entire ecosystem multifunctionality. The functional trade-off intensities of the aboveground, underground, and entire ecosystems showed significant V-shaped changes with shrub expansion. Shrub expansion improved plant species richness and changed the assembly process and species richness of soil abundant and rare subcommunities. Plant species diversity had a greater impact on multifunctionality than soil microbial diversity by more than 16%. The effect of plant species diversity on functional trade-offs was only one-fifth of the effect of soil microbial diversity. The soil microbial species richness did not affect multifunctionality, however, the assembly process of soil microbial communities did.Rather than the assembly process of soil microbial communities, the soil microbial species richness affected functional trade-offs.Our study is the first to couple multitrophic community assemblies to multifunctionality and functional trade-offs. Our results would boost the understanding of the role of aboveground and underground diversity in multifunctionality and functional trade-offs.